The Influence of Work Discipline and Local Culture on Employee Performance Mediated by Organizational Commitment - Zulkifli Zulkifli; Ibnu Khajar (Universitas Muhammadiyah Malang, 2026)
This study investigates how work discipline and local culture shape employee performance and whether organizational commitment mediates these relationships in an Indonesian organizational setting. Using a quantitative explanatory design, primary data were collected through a structured five-point Likert questionnaire from all employees of PT Delapan Jaya Propertindo, Palu City, Central Sulawesi (n=25) and analyzed using regression-based path analysis in SPSS, with mediation tested via the Sobel method. The model examines work discipline (X1), local culture (X2), organizational commitment/work commitment (Z), and employee performance (Y), operationalized through indicators of rule compliance, punctuality, and task responsibility (discipline); internalization of Kaili cultural values (local culture); affective and normative attachment (commitment); and quality, timeliness, and responsibility in work outcomes (performance). Instrument diagnostics supported analysis adequacy (all item r-counts > r-table=0.396; Cronbach’s alpha=0.776–0.815), while classical assumptions were met (Kolmogorov–Smirnov Sig.=0.200; VIF=1.41–1.61; Glejser Sig.=0.487–0.614). Hypothesis tests show that work discipline positively predicts employee performance (t=3.912; p=0.001), local culture positively predicts organizational commitment (t=4.235; p<0.001), and organizational commitment positively predicts employee performance (t=4.756; p<0.001). Mediation analysis confirms significant indirect effects through organizational commitment for both work discipline (Sobel z=2.97; p=0.003) and local culture (Sobel z=3.45; p=0.001), indicating partial mediation. Theoretically, the findings extend behavioural-control and socio-cultural perspectives by demonstrating that cultural values strengthen performance primarily by fostering commitment, while discipline influences performance both directly and via commitment. Practically, managers should combine consistent disciplinary systems with culturally grounded practices to build commitment and sustain performance. Overall, the study highlights organizational commitment as a pivotal mechanism linking formal rules and local values to employee performance in localized Indonesian workplaces.